Improving the Training of Future Specialists in Accounting and Taxation through the Implementation of the Conception of Dual Education - Izmaylov Yaroslav O.; Osmyatchenko Volodymyr O. (Bìznes Inform, 2019)
The article is aimed at generalizing the problems and developing proposals to improve the training of future specialists in accounting and taxation through the implementation of the dual education conception. A characterization of dual education is presented, which provides for the combination of training of persons at educational institutions with training in the workplace (at enterprises, institutions and organizations) to obtain a certain qualification, as usually on a contractual basis. The practical experience of implementing the reform of public finances in Ukraine through the implementation of the country’s first pilot project of dual form of education on the basis of the developed by the University of the State Fiscal Service of Ukraine education and professional master’s training program «Fiscal Administration». Proposals for improving the content-quality intensity of the master’s programs on accounting and taxation are presented. The authors substantiate the need and recommendations for training in terms of English-language master programs with the definition of prospects and advantages for higher education applicants. It is proved that dual form of education will allow applicants of higher education: acquiring theoretical and practical competences with ensuring their successful combination; become formed as qualified specialists who have not only the proper professional level, but also the capability to work efficiently in a team, skillfully adapting to rapidly changing market conditions; mastering the intricacies of professional skills in the chosen type of activity; broadening horizons and improving critical thinking; attending lectures by leading scholars and mentors, as well as trainings with the practitioners from national and international companies; developing a positive attitude towards public bodies and public service; getting into professional «lifts»; turning routine bureaucratic work into a creative and interesting process; becoming a part and an instrument of reforms of the State administration of Ukraine.